Nordeste, identidade e imaginário: uma análise da série Amores Roubados - Dantas, Bianca de Sousa (2020)
As the region that has great symbolic potential, the Northeast has long been a space that generates narratives about its people, its culture and the way of life of those present. This research investigates how northeastern identity is published in Rede Globo's Amores Roubados (2014) series. For this, the study was divided into three chapters. The first deals with the Northeast, identity and the imaginary. The second addresses television, series and serialization in the Brazilian context. The third, finally, analyzes the Amores Roubados series using two methods: a content analysis, divided between categories that examine how visual resources of the Northeast and the psychological characteristics of its people; and a hermeneutical symbolic proposal by Durand (2001). When it comes to economic development, how is the Northeast shown in the serie? What relationships prevail between the characters? In relation to the imaginary, which symbols predominate?